(3JNejS CHjGJ GdTjN GdSgjdis - (3YR GdOjf YHO GdMejO Hf GdMSjf Hf YJjb Hf QTjbs; (3GdTjN GdSgjdjs
(3ChdgG (B:s
(3gPg ebGWjY ZRdjGJ bdjJ ai ChbGJ eJaQbI dCSHGH EbJVJgG s
(3BNQgG (B:s
(3eG JZfJf hQbkG ai GdhQb GdfVQ Ydi aQY HGfI ai GdYTi gPG BNQ eG hLOJg ai GdCUd Gdefbhd efg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs